The increase in autophagy induced by naringin alleviates Schwann cell apoptosis mediated by the AMPK/mTOR signalling pathway - Jianwei Lv; Duo Shan; Haobo Jia; Zengliang Wang (Journal of Orthopaedic Surgery and Research)
Abstract Background Peripheral nerve injury (PNI) is currently an intractable disease for clinical therapeutics. Schwann cells (SCs) play pivotal roles in peripheral nerve regeneration. Naringin, a natural flavonoid, has potent beneficial effects on peripheral neuropathy. Researchers have rarely reported whether naringin attenuates SC apoptosis and the relevant mechanisms. Therefore, this study aimed to evaluate the antiapoptotic effects of naringin on SCs and probe the potential molecular mechanisms involved. Methods An in vitro SC apoptotic model was established by culturing RSC96 cells in foetal bovine serum (FBS)-free medium, namely, serum starvation. SC apoptosis was assessed by TUNEL staining and flow cytometry. The activities of the mitochondrial apoptotic pathway and autophagy in SCs were detected by western blotting and immunofluorescence staining. The autophagy inhibitor 3-methyladenine (3-MA) and the AMPK inhibitor Compound C were used to investigate whether autophagy mediated by AMPK/mTOR signalling is involved in the regulation of SC apoptosis by naringin. Results The results showed that starvation induced SC apoptosis and blocked autophagic flux. Naringin ameliorated SC apoptosis under starvation conditions by increasing the autophagy activity mediated by the AMPK/mTOR cascade, as Compound C inhibited its autophagy-activating effect, and 3-MA reversed its antiapoptotic efficacy. Conclusions Naringin mitigated starvation-induced SC apoptosis by increasing autophagy, which was attributed to the regulation of the AMPK/mTOR pathway. This study provides evidence that naringin could be an effective alternative drug for promoting peripheral nerve regeneration.